PENGENDALIAN KUALITAS PEMOTONGAN KAIN SATEN PADA PROSES PEMBUATAN TAS DI HOME INDUSTRI X DI KABUPATEN SIDOARJO - Putri, Erni Puspanantasari (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2014)
purchasing power, making a number of craftsmen home industry in Sidoarjo either small,medium or produced in homes facing bankruptcy. Their products are not only competingwith a medium or large industrial products that use semi-modern machinery, but alsoimported products, especially from China and Vietnam which relying on cheaper productprices. Ironically, consumers now also its orientation, to model and quality. It which notowned by the craftsman home industry, because their manual production. With thiscondition, resulted in the emergence difficulties for home craftsmen in the industry toimprove and expand its business.With the variety of backgrounds, as described above, the purpose of this researchare to provide recommendations about the quality control, cutting sateen in the process ofmaking bags in the Home Industries X.Solving problems in this research using the method to determine the source ofvariation of the process, that is using the Control Chart of X-bar (average) and R(Range). The results showed that the value of Process Capability Index (Cp) in the HomeIndustry X has a value of Cp = 0.525 <1.00. This means that the process has a lowcapability to meet the specifications of the expected measurement. As well as with size ofKane Performance Index (Cpk = 0.367) were the criteria CPL = 0.367, or CPU = 0.682<1.00, which means that the process is not able to meet the lower specification limit(LSL) and upper (USL). With this condition, it is necessary to control the use of controlchart from the X-bar and R to monitor the ongoing process from time to time, to soquickly take corrective action, if any changes which not desirable in the process ofmaking bags at Home industrial X.Kata Kunci : Pengendalian Kualitas, Indek Kapabilitas Proses (Cp), Indeks Kinerja Kane(Cpk)